The attitude of community health nurses towards integration of traditional healers in primary health care in North-West Province - MD Peu; R Troskie; SP Hattingh (AOSIS, 2001)
South Africa is called "the rainbow nation" because it has so many different cultures. These have an impact on the provision of primary health care. The purpose of this research is to foster good relationships between community health nurses and traditional healers and to explore, identify and describe the attitude of community health nurses towards the integration of traditional healers into primary health care. A non-experimental, explorative and descriptive research strategy was designed to explore the working relationship between community health nurses and traditional healers. Data was collected using a structured questionnaire. Quantitative as well as qualitative data analysis techniques were adopted to interpret the findings. The results indicated that respondents demonstrated positive attitudes towards working with traditional healers, especially in the provision of primary health care. Positive opinions, ideas and views were provided about the integration of traditional healers into primary health care. Respect, recognition and sensitivity were emphasized by respondents.